Bio‐Derived Surface Layer Suitable for Long Term Cycling Ni‐Rich Cathode for Lithium‐Ion Batteries. Issue 47 (22nd October 2021) - Jo, Chang‐Heum; Voronina, Natalia; Kim, Hee Jae; Yashiro, Hitoshi; Yaqoob, Najma; Guillon, Olivier; Kaghazchi, Payam; Myung, Seung‐Taek
Abstract: Since Ni‐rich cathode material is very sensitive to moisture and easily forms residual lithium compounds that degrade cell performance, it is very important to pay attention to the selection of the surface modifying media. Accordingly, hydroxyapatite (Ca5 (PO4 )3 (OH)), a tooth‐derived material showing excellent mechanical and thermodynamic stabilities, is selected. To verify the availability of hydroxyapatite as a surface protection material, lithium‐doped hydroxyapatite, Ca4.67 Li0.33 (PO4 )3 (OH), is formed with ≈10‐nm layer after reacting with residual lithium compounds on Li[Ni0.8 Co0.15 Al0.05 ]O2, which spontaneously results in dramatic reduction of surface lithium residues to 2879 ppm from 22364 ppm. The Ca4.67 Li0.33 (PO4 )3 (OH)‐modified Li[Ni0.8 Co0.15 Al0.05 ]O2 electrode provides ultra‐long term cycling stability, enabling 1000 cycles retaining 66.3% of its initial capacity. Also, morphological degradations such as micro‐cracking or amorphization of surface are significantly suppressed by the presence of Ca4.67 Li0.33 (PO4 )3 (OH) layer on the Li[Ni0.8 Co0.15 Al0.05 ]O2, of which the Ca4.67 Li0.33 (PO4 )3 (OH) is transformed to CaF2 via Ca4.67 Li0.33 (PO4 )3 F during the long term cycles reacting with HF in electrolyte. In addition, the authors' density function theory (DFT) results explain the reason of instability of NCA and why CaF2 layers can delay the micro‐cracking during electrochemical reaction. Therefore, the stable Ca4.67 Li0.33 (PO4 )3 F and CaF2 layers play a pivotal role to protect the Li[Ni0.8 Co0.15 Al0.05 ]O2 with ultra‐long cycling stability. Abstract : Tooth‐enamel derived material is applied to the surface of Ni‐rich cathode material, and this layer gradually changes into a more stable material by reacting with HF in electrolyte, which is called fluorization. The cathode shows more stable battery characteristics than the bare electrode.